The Effect of Learning Motivation on Students’ Learning Outcomes In Islamic Cultural History at MTs NU 1 Marabahan - Rosalia, Sheila; Fadhilah, Muhammad; Munawarah, Munawarah (TA'DIBUNA: Jurnal Pendidikan Agama Islam, 2025)
This research is motivated by variations in learning motivation and student learning outcomes in the Islamic Cultural History (SKI) subject at MTs Nahdlatul Ulama 1 Marabahan, which indicates the need for empirical studies on internal factors that influence learning achievement. This study aims to determine the level of student learning motivation, describe IS learning outcomes, and analyze the influence of IS learning motivation on learning outcomes. Using a quantitative approach with a survey method, data were collected through a SKI learning motivation questionnaire and IS report card documentation, then analyzed using descriptive statistics, prerequisite tests, Pearson correlation, and simple regression. The results showed that student learning motivation was in the medium-high category (73.13%), and IS learning outcomes were in the good category with an average of 79.69. There was a positive and significant influence between learning motivation and learning outcomes with a correlation coefficient of r = 0.55 and a contribution of 30%. This study concluded that learning motivation is an important factor in improving IS achievement and provides scientific contributions related to strengthening students' internal factors in Islamic religious education learning.